Recalibration of calculated VO2max against measured VO2max - Engvall, Jan (Linköping University, 2021)
This datafile describes how to recalculate peak work capacity at bicycle stress testing to an estimation of maximal oxygen uptake based on heartrate and load at peak exercise, and compares with actual measurement of VO2.

The dataset was originally published in DiVA and moved to SND in 2024.

Datafilen beskriver hur man räknar om maximal arbetskapacitet vid cykelbelastningstest till en uppskattning av maximal syreupptagningsförmåga baserat på hjärtfrekvens och belastning vid maximal ansträngning, och jämför med faktisk mätning av VO2.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Recalibration of calculated VO2max against measured VO2max
Calculated vs measured VO2max
Keywords: functional measurement; functional measurement; strain; strain; remodelling; remodelling; Cardiac adaptation; Cardiac adaptation; Physiology and Anatomy; Fysiologi och anatomi